Livestock transitions: Global options and local realities for adaptation and mitigation - Crane, Todd A. (International Livestock Research Institute, 2022)
Presentation by Todd Crane on climate action options in Africa's Livestock Systems. Presented at the United Nations Framework Convention on Climate Change (UNFCC) COP 27 at Sharm el-Sheikh, Egypt, November 2022.